2016
DOI: 10.1089/vim.2016.0056
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Does Not Impede Survival or Induction of Antibody Responses to Primary and Heterosubtypic Influenza Infections in Mice

Abstract: Impairment of immune defenses can contribute to severe influenza infections. Rapamycin is an immunosuppressive drug often used to prevent transplant rejection and is currently undergoing clinical trials for treating cancers and autoimmune diseases. We investigated whether rapamycin has deleterious effects during lethal influenza viral infections. We treated mice with two concentrations of rapamycin and infected them with A/Puerto Rico/8/1934 (A/PR8), followed by a heterosubtypic A/Hong Kong/1/68 (A/HK68) chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 30 publications
4
5
0
Order By: Relevance
“…Overall, our data support the concept that mTOR signaling plays a protective role in IAV-induced lung inflammation [13]. The higher viral load on day 10 post-infection (Fig.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Overall, our data support the concept that mTOR signaling plays a protective role in IAV-induced lung inflammation [13]. The higher viral load on day 10 post-infection (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Our results indicate that sirolimus administration causes more severe weight loss associated with increased viral replication. Overall, our data support the concept that mTOR signaling plays a protective role in IAV-induced lung inflammation [ 13 ]. The higher viral load on day 10 post-infection (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As an immunosuppressant drug, improper medication is not conducive to achieve the homeostasis of immune response, which not only inhibits excessive immune response, but also does not impede cellular and humoral responses to promote virus clearance. The dosage of sirolimus used in our study (initial dosage, 0.6 μg/g; maintenance dosage, 0.3 μg/g) was similar to those used in a clinical trial (2 mg/day) and previous studies in mice (0.6–1 μg/g) which indicated the protective roles of sirolimus [ 17 , 18 ]. Moreover, using different virus strains and infective doses may lead to different results.…”
Section: Discussionsupporting
confidence: 63%
“…It was reported that sirolimus combined with oseltamivir and corticosteroid treatment decreases viral titer and improves respiratory function in patients with severe H1N1 virus-induced pneumonia [ 17 ]. Furthermore, sirolimus contributes to delay the onset of morbidity in PR8 virus-infected mice [ 18 ]. Moreover, everolimus, a derivative of sirolimus, significantly reduces viral titer, lung weight, and hemorrhage score in H5N1 virus-infected mice [ 19 ].…”
Section: Introductionmentioning
confidence: 99%